Los usuarios en el archivo general de la UNED - Valdehita Mayoral, Mª Teresa (Revista General de Información y Documentación, 2008)
The article is about the users of the Archive of a public university of an international scope. The UNED is implanted in all the Independent Communities trough sixty Centers Associate. With presence in twelve countries of Europe, America and Africa by means of the support centers. All the educational administrative or investigation activities have their reflection in the documentation that is kept in the archives. The file keeps the documents that serve as test, the evidences which they give testimony of our acts in paper and electronic support.